Measurement of nitric oxide production by the lesioned rat retina with a sensitive nitric oxide electrode. - Groppe, M; Thanos, S; Schuhmann, W; Heiduschka, P (2003)
Nitric oxide (NO) plays multiple roles in the nervous system. It is produced as a result of damage or injury of the retina as a part of the central nervous system. Detailed knowledge of the extent and the time course of NO production is of great importance for the understanding of pathological processes and their appropriate medical treatment. Sections of rat retina were stained with antibodies against the three isoforms of NO synthase (NOS) at several time points after a lesion of the optic nerve. No significant changes of NOS expression could be seen at any of the checked time points. For the electrochemical detection of NO production, we modified small platinum electrodes with a NO-sensitive nickel porphyrin by electrochemical polymerisation. Compared to other substances, electrochemically polymerised eugenol was found to be most suitable for protection against interferences. For the measurements, differential pulse amperometry was used. The response to nitric oxide was linear.NO production of adult rat retinas was measured post axotomy after different time points with electrochemical electrodes ex vivo. With non-treated retinas, an NO concentration of approximately 15 microM was measured. NO concentration is elevated after an axotomy reaching its highest value of up to 30 microM 5 days after the lesion. The NO concentration is decreased below the initial value after 9-14 days post axotomy.